The Impact of Increased Electricity Consumption on the Indonesian Economy: An Input-Output Table Analysis - Puspita, Anggi Dwi; Prasetio, Heru Aryo; Sembiring, Lia Devita Malem; Kartiasih, Fitri (Jurusan Akuntansi Politeknik Negeri Bandung, 2026)
Despite the strategic role of energy in economic development, limited evidence exists on how electricity demand propagates across sectors within updated production structures in Indonesia. This study aims to analyze intersectoral linkages, identify leading sectors, and assess the economic impact of increased electricity consumption in Indonesia using the 2024 Input–Output approach. The results identify Manufacturing, Electricity and Gas Supply, and Transportation and Storage as leading sectors with strong intersectoral linkages. A simulated final demand shock of IDR 33.545 trillion generates a total output increase of IDR 92.503 trillion, with the largest impact on the electricity sector and significant spillover effects on mining and manufacturing. This study contributes by providing empirical evidence on energy demand shocks transmission interconnected production system, highlighting the dual role of energy as both a production input and a demand driver. The findings offer important implications for prioritizing energy sector development to support sustainable economic growth.